Sovereign wealth fund investment in venture capital, private equity, and real asset funds - Douglas J. Cumming; Pedro Monteiro (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
This paper examines the performance of 538 sovereign wealth fund (SWF) investments into venture capital, private equity, and real asset funds ("alternative asset funds") from 52 countries around the world over the years 1995-2020. The data indicate SWFs are significantly slower to fully liquidate and earn lower returns from their investments, particularly from their investments in venture capital funds. The longer duration and lower performance of SWFs is more pronounced for strategic SWFs than savings SWFs. We show that venture capital fund investments are more likely to be in countries with lower quality disclosure indices. SWFs are more often in buyout funds, and in larger funds with a greater number of limited partners. SWF performance is enhanced by having different types of institutional investors in the same limited partnership. Overall, the data indicate sovereign wealth funds make large investments in alternative asset funds with a longer-term view and earn a lower financial return consistent with strategic and political SWF investment motives.
urn:nbn:de:hebis:30:3-689933
Keywords: 330; Sovereign wealth funds; Strategic investors; Active investors; Delegated portfolio management; Limited partnerships